UI/UX Design of a QR Code and Geolocation-Based Attendance System Using Design Thinking and Prototyping Methods - Atma, Yori Adi; Ganiyu, Ahmad Rizki Akbar; Arsyah, Ulya Ilhami; A'yunin, Qurhata; Fryonanda, Harfebi (ABEC Indonesia, 2024)
Student attendance is an important element in ensuring proper presence and participation in the academic environment. However, in the Information Technology Department of Padang State Polytechnic, the attendance process is still conducted manually, which leads to various issues such as the potential for cheating, inaccuracies in recordkeeping, and paper waste. This research aims to address the issue by designing and developing a QR code and geolocation-based attendance system using the Design Thinking and Prototype methods. The Design Thinking method is used to explore and understand user needs, while the Prototype method is employed to develop and test solutions iteratively. The system produced is expected to improve the accuracy of attendance recording, reduce fraud, and minimize resource waste. In addition, this research contributes to creating a more efficient, reliable, and user-friendly attendance system, particularly in academic settings.